Urinary Peptide Analysis Differentiates Pancreatic Cancer From Chronic Pancreatitis. Issue 7 (August 2016) - Schönemeier, Bastian; Metzger, Jochen; Klein, Julie; Husi, Holger; Bremer, Birgit; Armbrecht, Nina; Dakna, Mohammed; Schanstra, Joost P.; Rosendahl, Jonas; Wiegand, Johannes; Jäger, Mark; Mullen, William; et al.
Abstract : Objectives: Differentiation of pancreatic cancer (PCA) from chronic pancreatitis (CP) is challenging. We searched for peptide markers in urine to develop a diagnostic peptide marker model. Methods: Capillary electrophoresis–mass spectrometry was used to search for peptides in urine of patients with PCA (n = 39) or CP (n = 41). Statistical different peptides were included in a peptide multimarker model. Peptide markers were sequence identified and validated by immunoassay and immunohistochemistry (IHC). Results: Applied to a validation cohort of 54 patients with PCA and 52 patients with CP, the peptide model correctly classified 47 patients with PCA and 44 patients with CP (area under the curve, 0.93; 87% sensitivity; 85% specificity). All 5 patients with PCA with concomitant CP were classified positive. Urine proteome analysis outperformed carbohydrate antigen 19-9 (area under the curve, 0.84) by a 15% increase in sensitivity at the same specificity. From 99 healthy subjects, only four were misclassified. Fetuin-A was the most prominent peptide marker source for PCA as verified by immunoassay and IHC. In silico protease mapping of the peptide markers' terminal sequences pointed to increased meprin-A activity in PCA, which in IHC was associated with neoangiogenesis. Conclusions: Urinary proteome analysis differentiates PCA from CP and may serve as PCA screening tool. Abstract : Supplemental digital content is available in the text.